Write Speech Text Learning Using the Audio Visual Media - Rahmawati, Nina Septia (Universitas Negeri Padang, 2019)
Good learning is learning that is equipped with appropriate learning media to achieve learning goals. Conformity includes suitability of the needs of students, local environmental conditions, and the ability of teachers. A good learning media is media that can facilitate the achievement of learning objectives. Learning to write speech texts for junior high school class IX students requires learning media as a means of supporting the ease of achieving learning goals. Along with the development of science and technology, students' needs for learning media are also growing. Students prefer and are more interested in IT-based learning media (science and technology) in the form of audio-visual media. Students prefer to see/observe objects to stimulate ideas in writing speech texts.